Colección y caracterización agronómica de ecotipos de sábila aloe vera l. de la región sur del país - Aguilar Azanza, Patricio Rodrigo (2006)
In order to study the genetic behaviour of five ecotypes of Sabila Aloe vera, an essay was carried out at the southern region of Ecuador, which includes Loja and El Oro provinces, with similar ecologic zones. The trial comprised the last three months of 2005 and the first months of the actual year. The objectives planned for this essay were: 1. To collect five ecotypes of Sabila from the southern region of the country. 2. To characterize agronomicaly at least five ecotypes of Sabila and to determine its productive potential. Taking as reference a chart elaborated by the Geographic Military Institute for the southern region of the country, there were limited the climatic zones at the altitudinal ground below 2000 masl, for visiting the rural areas seeking genetic material. From this field trial, there were collected shoots at the Vilcabamba Valley, El Tambo and Playas, belonging to Loja province, and they were named taking in account the collecting site. At El Oro province there were collected two genetic materials. Arenillas and Machala, accounting with five ecotypes for sustain this essay. At the Botanic Garden belonging to the Agropecuary Sciences Faculty, the material was planted in plots under a design of Blocks at Random with four reapplications. The analyzed variables studied to characterize and to study the agronomic behaviour were: size of the fleshy leaf, distance between spines at the edge of the leaf, size of spines, number of external leaves, height of plant, mucilage yield per plant, weight of leaves and weight of plant. The obtained results evidenced that the genetic material studied corresponded to different populations, according to Duncan and F Tests, selected for analyze the collected data. As referred to ecotypes, the best for mucilage production was the so named Machala, with yields of 246,4 g/plant and a weight of plant of 1638 g; this ecotype together with the material from Arenillas are the best optioned for the propagation to establish commercial cultivars.